(untitled) (Academic Journal of Internal Affairs, 2021)
The coronavirus pandemic meant an unexpected challenge both for the world and for the health care system of the Hungarian Prison Service. Based on study of the legal environment and the knowledge gained about the virus, it was necessary to rewrite the operation of the Hungarian Prison Service in order to preserve the health of the prison staff and the prisoners in the best way and to the greatest extent. Substantial measures had to be taken to reduce the risk of transmission of the infection by both staff members and new detainees significantly, and to prevent the spread of the pandemic within the institutions effectively, while maintaining lawfulness and safety of detention. A transformation of the prison service supply system had to be organized to ensure the rapid investigation of suspected infections and to grant adequate health care for all sick inmates quickly. The paper presents the legal environment of the prison service health care system, the most important characteristics of the SARS-CoV-2 virus causing the pandemic, and the health and epidemiological measures taken in order to maintain control and defence. I will present methods used to control the epidemic in the prisons, the strict rules that were applied for prisoners as a closed community and the measures taken to support prison staff and to protect their health.